2023
DOI: 10.1021/acs.joc.2c03062
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-Difluoromethylene Ethers via Photoredox-Induced Hyperconjugative Ring Opening of gem-Difluorocyclopropanes

Abstract: Fluorinated compounds have found widespread applications in pharmaceuticals, agrochemicals, and materials science. Precise construction of α-difluoromethylene ether (CF2 –O) moiety in organic molecules is of high demand. Herein, a visible light-promoted reaction protocol for the synthesis of α-difluoromethylene ether from gem-difluorocyclopropane is described. The key ring-opening step is induced by hyperconjugative interaction of cyclopropane with photo-oxidized aromatic rings. This reaction is easy scale-up,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…5 In the past two decades, these advancements have primarily focused on two types of ring-opening modes: proximal C1–C2 bond cleavage and distal C2–C3 bond cleavage (Scheme 2). Photocatalysis and organocatalysis enable the cleavage of the C1–C2 bond via oxidative C–C bond activation to generate C1 and C2 difunctionalized products (Scheme 2, a and b), 6 while a homolytic substitution induced by the bromine radical gives C2 and C3 difunctionalized products (Scheme 2, c). 7 Because of the distortion of orbitals through the fluorine effect and the ring strain, the C2–C3 bond can easily interact with the TM-complex to result in a fluoroallyl TM species via a sequence of oxidative addition and β-F elimination, which ultimately reacts with nucleophiles to provide allylic products (Scheme 2, d).…”
Section: Introductionmentioning
confidence: 99%
“…5 In the past two decades, these advancements have primarily focused on two types of ring-opening modes: proximal C1–C2 bond cleavage and distal C2–C3 bond cleavage (Scheme 2). Photocatalysis and organocatalysis enable the cleavage of the C1–C2 bond via oxidative C–C bond activation to generate C1 and C2 difunctionalized products (Scheme 2, a and b), 6 while a homolytic substitution induced by the bromine radical gives C2 and C3 difunctionalized products (Scheme 2, c). 7 Because of the distortion of orbitals through the fluorine effect and the ring strain, the C2–C3 bond can easily interact with the TM-complex to result in a fluoroallyl TM species via a sequence of oxidative addition and β-F elimination, which ultimately reacts with nucleophiles to provide allylic products (Scheme 2, d).…”
Section: Introductionmentioning
confidence: 99%
“…15 reacting with alcohols. 17 The key reaction step involves the photooxidation of gem-difluoroalkenes to form radical cations, which can be trapped by alcohols to form a CF 2 −O bond. However, the reaction is limited to substrates with an electronrich aryl substituent on the cyclopropane ring.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, constructing of the CF 2 -O bond with aliphatic alcohols is more challenging. Previously, we reported a photoredox-induced ring-opening of gem -difluorocyclopropanes to construct the CF 2 –O bonds by reacting with alcohols . The key reaction step involves the photooxidation of gem -difluoroalkenes to form radical cations, which can be trapped by alcohols to form a CF 2 –O bond.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Very recently, Hu and co-workers delineated a visible lightmediated CÀ C bond cleavage of gem-difluoro cyclopropanes to generate difluoro methylene ethers (Scheme 2B). [16] In the last decade, electro-organic synthesis has emerged as a useful method for performing advantageous organic transformations [17] to achieve specific oxidative or reductive reactions such as decarboxylation, [18a] alkene bifunctionalization, [18b] rearrangements, [18c] annulations, [18d] and CÀ C or C-heteroatom bond formation. [18e-i] In 2021, Lei et al demonstrated cyclopropanes CÀ C bond cleavage to produce 1,3-bifunctionalized compounds electrochemically (Scheme 2B).…”
mentioning
confidence: 99%
“…Based on the above control experiments and previous literature reports, [10][11][12][13][14][15][16][19][20] Further, to expedite the effective synthesis of an oxo-fluorinated molecule, we wondered if the styrene cyclopropanation and our ring-opening functionalization could be combined. Fortunately, we were able to integrate our oxofluorination with the cyclopropanation method, giving us immediate access to the desired product in a 30% yield (Scheme 7a).…”
mentioning
confidence: 99%